Asuhan Keperawatan Pada Ibu Post Sectio Caesarea Untuk Menurunkan Intensitas Nyeri Dengan Tindakan Foot Massage - aryanti, dewi; Fauziah, Lutvia (Universitas Banten Jaya, 2024)
Sectio Caesarea (SC) is a delivery with specific indications that require a surgical method on the abdominal wall to remove the baby. Sectio caesarea causes pain due to the release of histamine and prostaglandins. For this reason, non-pharmacological interventions are needed to help reduce pain, including the foot massage technique. This study aims to determine the effect of foot massage techniques on reducing pain intensity. The number of samples in this study amounted to 2 respondents. This research was conducted on April 11-16, 2023. The instrument used is a numerical rating scale (NRS). The type of design of this research is descriptive with a case study report. Foot massage technique in post sectio caesarea mothers carried out 6x implementation for three days and done 2x a day. The results of this study indicate that foot massage can reduce pain levels in both respondents. The First respondent before being given the foot massage pain scale (6) after being given the foot massage pain scale becomes a pain (2), and the second respondent before being given the foot massage pain scale (6) after being given foot massage pain scale becomes (1). The conclusion obtained in this study is that the foot massage technique can reduce the pain scale and can be used as an alternative to non-pharmacological management in pain management.